A Semiotic Analysis of Sign Found in GOJEK Advertisement ‘Jangan Sepelekan Kekuatan Jempol’ - Intan Aulia Rahman, Ajie; Astuti, Asri; Khoirunisa, Eva; Fitriyah, Fitriyah; Azzahrani, Marsya; Sakinah, Mutiara (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research analyzes the denotation, connotation, and myth present in GoJek advertisements through the lens of Roland Barthes' semiotic theory. Employing a qualitative descriptive methodology, the study interprets the imagery within the GoJek advertisement video. The analysis adheres to the data flow model by Miles and Huberman (1994), which encompasses data reduction, display, and conclusion formulation. The results indicate that the thumb serves as a central symbol in the GoJek advertisements. On a denotative level, it signifies physical actions like using a smartphone, wiping tears, counting money, and utilizing the GoJek application. On a connotative level, the thumb is linked to themes of empowerment, efficiency, social connectivity, and resilience. The research further uncovers various myths associated with the thumb symbol, including narratives about modernity, progress, individual potential, and the impact of small actions on communal well-being. By utilizing Barthes’ semiotic framework, this study emphasizes how GoJek advertisements leverage visual signs to convey persuasive messages that resonate with the intended audience within their cultural and social context.